Application of 3D biological nano scaffold materials in the health treatment of foot and ankle sports. (12th April 2021) - Ren, Rong; Ji, Junhua; Ding, Junwen; Li, Zhaowei; Tao, Shuaixian; Li, Zeqing
Bone tissue is an important part of the human body and plays an indispensable physiological function. Damage to bone tissue will have a serious impact on the health of patients. Three types of MGPC scaffolds were prepared using 3D printing technology. The macroscopic, microstructure, and histology of the three scaffolds were observed under an electron microscope. The cells grew normally and spread well. Rat L-929 fibroblasts were cultured in three scaffold extracts, and the cells were cultured with DMEM as a control. Cell proliferation was detected by cell counting. Scanning electron microscopy of the cell-scaffold complex revealed that a large number of chondrocytes adhered and grew on the surface of the MGPC scaffold. With the increase of culture time, the number of cells in each group showed an increasing trend. MGPC has no cytotoxicity, excellent physical and chemical properties, and is expected to become a biological scaffold material.